Balanced ambipolar organic field-effect transistors by polymer preaggregation - Janasz, Lukasz; Marszalek, Tomasz (ACS applied materials & interfaces, 2017)
Ambipolar organic field-effect transistors (OFETs) based on heterojunction active films still suffer from an imbalance in the transport of electrons and holes. This problem is related to an uncontrolled phase separation between the donor and acceptor organic semiconductors in the thin films. In this work, we have developed a concept to improve the phase separation in heterojunction transistors to enhance their ambipolar performance. This concept is based on preaggregation of the donor polymer, in this case poly(3-hexylthiophene) (P3HT), before solution mixing with the small-molecular-weight acceptor, phenyl-C61-butyric acid methyl ester (PCBM). The resulting heterojunction transistor morphology consists of self-assembled P3HT fibers embedded in a PCBM matrix, ensuring balanced mobilities reaching 0.01 cm2/V s for both holes and electrons. These are the highest mobility values reported so far for ambipolar OFETs based on P3HT/PCBM blends. Preaggregation of the conjugated polymer before fabricating binary blends can be regarded as a general concept for a wider range of semiconducting systems applicable in organic electronic devices.